Hydrogen Evolution Reaction: Cofunction of Protons as Dopant and Reactant Activate the Electrocatalytic Hydrogen Evolution in Emeraldine‐Polyguanine (Adv. Mater. Interfaces 2/2020). Issue 2 (23rd January 2020) - Coskun, Halime; Aljabour, Abdalaziz; Schöfberger, Wolfgang; Hinterreiter, Andreas; Stifter, David; Sariciftci, Niyazi Serdar; Stadler, Philipp
Abstract : A DNA nucleobase is polymerized by oxidative chemical vapor deposition and applied in electrocatalytic hydrogen evolution reaction. The unique synthesis enables the polymerization and protonation of guanine to emeraldine‐polyguanine (ePG), analog to polyaniline with four additional and potentially catalytic‐active amino functions enhancing the reactivity. Moreover, protons coserve as dopant and reactant in the catalytic electroreduction of protons to molecular hydrogen. More details can be found in article number 1901364 by Halime Coskun and co‐workers.